2004
DOI: 10.1016/j.jcf.2003.12.008
|View full text |Cite
|
Sign up to set email alerts
|

β-defensins and LL-37 in bronchoalveolar lavage fluid of patients with cystic fibrosis

Abstract: The data suggest that concentrations of antimicrobial peptides are correlated with severity of CF lung disease: Levels of LL-37/hCAP-18 are associated with bronchial inflammation and, therefore disease severity, whereas decreased levels of beta-defensins in advanced lung disease likely contribute to a secondary defect of the local host defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 35 publications
2
107
2
3
Order By: Relevance
“…In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] . In addition, to our knowledge among all AMPs and sPLA2s reported in the literature, sPLA2-IIA displays the most potent and selective bactericidal action toward Gram-positive bacteria, such as SA.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] . In addition, to our knowledge among all AMPs and sPLA2s reported in the literature, sPLA2-IIA displays the most potent and selective bactericidal action toward Gram-positive bacteria, such as SA.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these antimicrobial peptides is locally induced at the sites of inflammation and infection within epithelial cells, and invading neutrophils represent an additional source of peptides (47,48). In this context, it has been reported that the concentrations of HNPs, hBDs and LL-37 are increased up to 40 μg/ml in bronchoalveolar and nasal fluids from patients with inflammation and infection (48)(49)(50). Importantly, we have demonstrated that LL-37, hBD-3 and HNP-1 can suppress neutrophil apoptosis in vitro at the concentrations (0.01-40 μg/ml) comparable to those at the sites of inflammation and infection (26,27) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the numbers of viable bacteria 6 hours after infection, the apical surfaces of the cultures were washed with 100 µl of PBS and serial dilutions were plated onto LB agar plates. 5 µg of recombinant hBD-2 in 200 µl 18 was applied to the apical surfaces of the cultures in some experiments based on concentrations calculated for airway secretions 19 …”
Section: Bacterial Survival Assaysmentioning
confidence: 99%